2007
DOI: 10.1097/ana.0b013e3181557471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylactic Ondansetron on Postoperative Nausea and Vomiting in Patients on Preoperative Steroids Undergoing Craniotomy for Supratentorial Tumors

Abstract: The exact incidence of postoperative nausea and vomiting (PONV) in patients on steroids undergoing neurosurgical procedures is not known. This prospective randomized double-blind study was planned to know the efficacy of prophylactic ondansetron in the prevention of PONV in patients on steroids as compared with placebo. Seventy adult patients of either sex who had received preoperative steroids (dexamethasone) for at least 24 hours and were scheduled to undergo craniotomy for supratentorial tumors were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…16 Koc¸et al, 20 found that the combination of 800 mg of oral gabapentin and 8 mg of IV dexamethasone administered 1 hour before varicocele surgery provided better PONV and postoperative pain control as compared with placebo or either drug alone. Studies in craniotomy patients have also demonstrated that the combination of dexamethasone with aprepitant (NK-1 receptor antagonist), 17 or ondansetron (5HT 3 receptor antagonist), 21 provides better control of PONV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Koc¸et al, 20 found that the combination of 800 mg of oral gabapentin and 8 mg of IV dexamethasone administered 1 hour before varicocele surgery provided better PONV and postoperative pain control as compared with placebo or either drug alone. Studies in craniotomy patients have also demonstrated that the combination of dexamethasone with aprepitant (NK-1 receptor antagonist), 17 or ondansetron (5HT 3 receptor antagonist), 21 provides better control of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that a combination of dexamethasone with NK-1 or 5HT 3 receptor antagonists reduces the incidence of PONV after craniotomy. 17,21 Dexamethasone in combination with gabapentin has also been shown to reduce the incidence of postoperative pain in patients undergoing varicocele surgery. 20 The antiemetic effect of gabapentin has not been previously evaluated in patients undergoing craniotomy.…”
mentioning
confidence: 99%
“…Los medicamentos específicos son: dolasetrón (reduce el vómito) [23][24][25][26][27] , granisetrón (reduce el vómito) 28-32 y ondansetrón (reduce el vómito y rescates antieméticos) [28][29][30][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
Section: Antieméticos 5ht3unclassified
“…However, these agents have been reported to have adverse effects such as excessive sedation, hypotension, dysphoria, hallucinations, and extrapyramidal signs [1,5,12,13], all of which are undesirable for neurological assessment after neurosurgical operations. Selective 5-HT 3 receptor antagonists (ondansetron, granisetron, and tropisetron) are effective in PONV after craniotomy without neurological adverse effects [1,3-5,7,11,14-17]. Ramosetron, a selective 5-HT 3 receptor antagonist, has been used effectively in various surgical procedures for the prevention or treatment of PONV [18].…”
Section: Introductionmentioning
confidence: 99%